Reformasi Pemahaman Teori Maqasid Syariah (Analisis Pendekatan Sistem Jasser Audah) - Muhammad Iqbal Fasa (Hunafa: Jurnal Studia Islamika, 2016)
This paper attempts to offer reform ideas Jasser Auda thought related reforms theoretical understanding of maqᾱṣid sharia. The systems approach is done by Auda critize the theory of classical maqᾱṣid more likely to hierarchical and narrow mindset. The classical maqᾱṣid pressure a point more on protection and preservation. Whereas the new maqᾱṣid theory emphasizes development (construction, development) and rights (rights). Thus, Auda developed the concept of human development as the main target of maslahah (public interest). Auda offers the systems approach, namely: cognitive nature; interrelated; wholeness; openness; multi dimentionality and purposefulness. At the end of the discussion in this paper, the authors develop the idea of Jasser Auda by offering Sharia Maqᾱṣid concept in the context of Islamic Economics